2017
DOI: 10.4168/aair.2017.9.5.403
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Treatment of Allergic Rhinitis According to Nasal Cytology

Abstract: PurposeNasal cytology is important in the diagnosis and treatment of nasal inflammatory diseases. Treatment of allergic rhinitis (AR) according to nasal cytology has not been fully studied. We plan to explore the individualized treatment of AR according to nasal cytology.MethodsNasal cytology from 468 AR patients was examined for inflammatory cell quantity (grade 0-5) and the percentage of neutrophils and eosinophils. Results were subdivided into the following categories: AR(Eos), eosinophil ≥50% of the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…In allergic rhinitis and asthma, eosinophils are recruited by pro-inflammatory cytokines and mediators and are the predominant cells in later phases of an allergic response ( 30 , 31 ). The role of neutrophils in allergic inflammation is debated, but some studies report increasing numbers in nasal cytology in patients with allergic rhinitis ( 32 34 ). While all five tested subjects reported recurrent or chronic symptoms of allergic rhinitis and nasal samples were collected during the peak pollen season, none had increased numbers of eosinophilic, neutrophilic or lymphocytic nasal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In allergic rhinitis and asthma, eosinophils are recruited by pro-inflammatory cytokines and mediators and are the predominant cells in later phases of an allergic response ( 30 , 31 ). The role of neutrophils in allergic inflammation is debated, but some studies report increasing numbers in nasal cytology in patients with allergic rhinitis ( 32 34 ). While all five tested subjects reported recurrent or chronic symptoms of allergic rhinitis and nasal samples were collected during the peak pollen season, none had increased numbers of eosinophilic, neutrophilic or lymphocytic nasal cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of nasal cytology in 468 AR patients described a neutrophils dominated (≥90%) inflammatory cell response in 14.32% and a mixed eosinophil/neutrophil (10% ≤ eosinophil < 50%) response in 23.93% of all cases. [ 88 ]. Compared to healthy controls higher neutrophil numbers are generally observed in nasal fluid of AR patients [ 49 ].…”
Section: Blood Cells In Armentioning
confidence: 99%
“…Whereas, neutrophils exerts its role in remodeling by secreting remodeling mediators, such as MMPs and TGF-β in non-eosinophilic CRS [ 23 ]. AR is a Th2-skewed inflammation with high levels of IL-4, IL-13 and IL-5, and elevated inflammatory cells infiltration including EOS and neutrophils [ 24 ]. Studies suggested that AR could affect the pathogenesis of CRS and the effects could be different between distinct races.…”
Section: Discussionmentioning
confidence: 99%